Unveiling the Semiotics of Cigarette Advertising: Analyzing Propaganda Strategies - Tano, Andreas; Simanjuntak, Immanuel Sheva (Jurnal Pendidikan Makarios, 2023)
This study aims at demonstrating how prolonged exposure to media, particularly in cigarette ads, can shape individuals' beliefs, attitudes, and values. The cultivation theory by Gerbner, G. (1998) was applied in the analysis to show the mentioned issues. Besides, the study also investigated the role of cinematography, specifically cameraworks, and employed a semiotic approach to explore signs and symbols in the ads. Ferdinand de Saussure's (1916) "signifier" and "signified" framework was used to illustrate how visual elements construct narratives, shedding light on how cigarette ads subtly influence perceptions of smoking and its lifestyle implications. Based on the analysis, it can be concluded that: 1) It is revealed that extensive exposure to media, including cigarette ads, distorts perceptions of smoking's prevalence and harm, potentially influencing initiation or continuation of smoking behaviors. 2) Cinematography, analyzed through semiotics, unveils how visual elements in cigarette ads construct intricate narratives. The interplay of "signifier" and "signified," rooted in Saussure's framework, showcases how camera techniques convey nuanced implicit and explicit meanings. 3) Cigarette ads employ a dual-layered approach, blending explicit messages of courage with implicit motives of empowerment. Regular media consumers are more inclined to perceive these messages as reflective of reality. The examination illustrates the interrelated aspects of cinematography, and semiotics, discussed by using cultivation theory in molding the complex issues of cigarette advertisements. The interaction among these components impacts how viewers perceive, shape stories, and nurture distinct convictions and viewpoints.